Teorema Kecil Fermat (Fermat’s Little Theorem) - Dini Wahyuningsih (Jurnal Pustaka Cendekia Pendidikan, 2025)
Fermat's Little Theorem is a fundamental theorem from the realm of number theory. Even by using this theorem, we can derive Euler's Theorem with the help of the properties of the Euler function φ, even though actually Fermat's Little Theorem is a special case of Euler's Theorem. Then Fermat's little theorem (Fermat's little theorem) is a form of Number Theory, which is a branch of Mathematics that discusses various things about numbers. In number theory there is a chapter that discusses three mathematicians who were very useful in the development of number theory. Fermat's theorem is not a grand theorem, in 1622 Pierre de Fermat made a theorem that made him very famous, which is now known as Fermat's little theorem. Fermat's little theorem (Fermat's little theorem) to determine the primeness of a number. In general, Fermat's little theorem is used to find the remainder of division of a number by a prime number.